Majlis Ta’lim: Institution for Strengthening Islamic Moderation - Muh. Hafidz (Lakpesdam PCNU Kota Salatiga, 2020)
This article aims at answering the questions on how the strategy used by majlis ta’lim developed in the Nahdliyyin community in strengthening Islamic moderation in this globalization era, and what are its advantages as a non-formal institution. In terms of answering these questions, the writer used the technique of collecting the data through interviews and observation. Considering that this study tends to be traditional, there is no need for written documents. The interview was conducted with the Muslim figures as activists of majlis ta’lim, and the observation was carried out through joining the recitation held by Muslimat. The collected data show that majlis ta’lim is a strategic place for strengthening and building Islamic moderation. Its strategy is carried out in several ways. First, inviting Islamic moderation figures to majlis ta’lim. Second, determining moderate themes as the main focus of the recitation. Third, optimizing majlis ta’lim as a massive movement. The advantages of majlis ta’lim as one of the public forums for Muslim community are: First, majlis ta’lim is a forum for education and teaching followed by its members. Second, the emotional relation among those members is stronger as compared to those in other forums. Third, the recitation in majlis ta’lim makes no difference in the profession, occupation, and position of the members.